Massive Subcutaneous Emphysema and Pneumothorax in a Case of Attacked by a Domesticated Bull – An Autopsy Based Diagnosis - Singh, PK; Shah, DK (Kathmandu University Medical Journal, 2023)
Subcutaneous emphysema is a condition when air or gas gets trapped within the subcutaneous layer. It is characterised by crackling feeling on palpation of the skin known as subcutaneous crepitation which is described as touching rice krispies. A 70 years male from hilly region of Nepal with agricultural background suffered multiple injuries sustained due to an attack by domesticated bull in his house. Upon the incident the injured male was taken to hospital, where he was declared “Brought Dead” by the Emergency Department of Dhulikhel Hospital, Kathmandu University Hospital. His body was brought for autopsy in Department of Forensic Medicine and Toxicology of Kathmandu University School of Medical Sciences. On complete autopsy, massive subcutaneous emphysema and pneumothorax was demonstrated. The details of finding are discussed in detail as follows.